WIFE BEATING IN SOCIAL AND LEGAL PERSPECTIVE IN INDONESIA - Noni Zulkarnain; Dian Rizki; Sri Istiawati; Saniah Saniah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study aims to determine the act of wife beating according to the views or perspectives of sociology and law in Indonesia and also to find out the thoughts and understanding of Law Number 23 of 2004 concerning the Elimination of Domestic Violence in terms of loading on sanctions for perpetrators of wife beating. The techniques used in data collection through normative research and social aspects are further methods of collecting matari and literature data from, legislation, and various reading sources with national and international integration, used analysis techniques in qualitative form. The conclusion obtained is that in terms of sociology and law in Indonesia the act of beating a wife is an act that is prohibited both in terms of sociology and law, but in the application in society there is still a development of misunderstanding and ignorance in this matter. In solving the problem, the presence of regulations of Law No. 23 of 2004 concerning the Elimination of Domestic Violence is not only seen, read and heard but also implemented properly, because it requires a combination of personal and social matters, and is supported by a strict legal system in taking action against the perpetrator, providing very strict legal sanctions and also appropriate for those who commit acts of wife beating in society so as to create a fair, peaceful and safe quality of life.